PERAN KENDANG DALAM SAJIAN MRABOT GENDHING REGENG LARAS PÉLOG PATHET BARANG - Nanda Indah Nur Risqia; Suyoto (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
This study discusses the role of the kendang in the performance of Gendhing Regeng in the mrabot form, tuned to pélog pathet barang. The research focuses on how the kendang is elaborated in relation to aspects of rhythm, tempo (laya), ornamental patterns (sekaran), and variations (wiledan). The aim is to describe the function of the kendang not only as a timekeeper but also as a structural and expressive element in the presentation of the gendhing. This study employs a qualitative method, with data collected through literature review, direct observation, and interviews with karawitan practitioners. The analysis applies the theory of garap and the concept of mandheg in Surakarta-style karawitan. The results indicate that the kendang functions as the controller of rhythm and tempo, while also shaping dynamics through accents, stresses, volume, and rhythmic patterns. In the inggah section, variations of mandheg are found in wiled and rangkep tempos, along with sekaran presented in several wiledan variations. Types of kendhangan such as matut, tangguh, and mungguh are employed to emphasize both light and heavy sèlèh, enriching the musical expression of the gendhing. Overall, the kendang plays not only a controlling role but also determines the character and aesthetic color of Gendhing Regeng in pélog pathet barang.